Molecular profile of avian pathogenic Escherichia coli (APEC) from poultry associated with colibacillosis in Algeria - LOUNIS, M.; ZHAO, G.; LI, Y.; GAO, Y.; WANG, J.; OUMOUNA, M.; OUMOUNA, K. (Journal of the Hellenic Veterinary Medical Society, 2020)
The objective of the present study was the detection of virulence-associated genes of E. coli isolated from chicken with colibacillosis. Seventeen (17) APEC isolates were examined by two panels of PCRs for the presence of 11 genes described for avian pathogenic (hlyF, iroN, iss, ompT, iutA and fimC) and diarrheagenic (eae, stx, est, elt, ipaH and aggR) E. coli. Results revealed that none of the APEC isolates harbored the genes eae, stx, est, elt, ipaH and aggR. In another hand, 88.2% of the isolates were positive for 3 or more of the virulence genes hlyF, iroN, iss, ompT, iutA and fimC. Also, 35.3% of the isolates harbored all the six genes. Genes fimC (88.2%), iss (82.3%) and ompT (76.5%) were the most prevalent while genes hylF, iutA and iroN which were present with the same frequency (52.9%) were mostly associated with highly pathogenic strains.